ChemInform Abstract: Palladacycles Derived from Arylphosphinamides for Mild Suzuki—Miyaura Cross‐Couplings. Issue 4 (January 2016) - Wu, Guo‐Jie; Han, Fu‐She; Zhao, Yu‐Long
Abstract: A wide variety of biaryls is synthesized through Suzuki—Miyaura cross‐coupling of aryl bromides or aryl triflates with (het)aryl boronic acids.